Dithiocarbamate-modified starch derivatives with high heavy metal adsorption performance. (20th January 2016) - Xiang, Bo; Fan, Wen; Yi, Xiaowei; Wang, Zuohua; Gao, Feng; Li, Yijiu; Gu, Hongbo
Graphical abstract: Highlights: Three types of dithiocarbamate (DTC)-modified starch derivatives were synthesized. Adsorption mechanism was proved by chelating between DTC groups with heavy metal. DTC-modified mesoporous starch showed superior adsorption ability for heavy metals. Abstract: In this work, three types of dithiocarbamate (DTC)-modified starch derivatives including DTC starch (DTCS), DTC enzymolysis starch (DTCES) and DTC mesoporous starch (DTCMS) were developed, which showed the significant heavy metal adsorption performance. The adsorption ability of these three DTC modified starch derivatives followed the sequences: DTCMS > DTCES > DTCS. In single metal aqueous solutions, the uptake amount of heavy metal ions onto the modified starches obeyed the orders: Cu(II) > Ni(II) > Cr(VI) > Zn(II) > Pb(II). The adsorption mechanism was proved by the chelating between DTC groups and heavy metal ions through the pH effect measurements. A monolayer adsorption of Langmuir isotherm model for the adsorption of Cu(II) onto DTCMS was well fitted rather than the multilayer adsorption of Freundlich isotherm model. The adsorption kinetics of Cu(II) onto starch derivatives was found to be fit well with the pseudo-second-order model. Additionally, in the presence of EDTA, the adsorption ability and uptake amount of heavy metal ions onto these three DTC modified starch derivatives is identical with the results obtained in the absence of EDTA.